Are dizziness/lightheadedness helpful symptoms for telephone triage of females and males calling the out-of-hours service for acute chest discomfort? A cross-sectional study - Frans H Rutten; Hester M den Ruijter; Sander van Doorn; Dorien L Zwart; Loes T C M Wouters; Anna S M Dobbe; Laurens van der Hem; D Carmen Erkelens (BMJ Open)
Objectives Symptoms of dizziness/lightheadedness are more often reported by females than males with an acute coronary syndrome (ACS). Therefore, we investigated if these symptoms are helpful for triage and diagnosis of ACS in females and males with acute chest discomfort.Design Cross-sectional study.Setting Nine out-of-hours service in primary care (OHS-PC) in the Netherlands participated, covering both rural and urban areas, serving a total population of 1.5 million people.Participants 2195 patients were selected calling the OHS-PC with acute chest discomfort, 55.4% were females. Calls were selected based on International Classification of Primary Care codes and keywords, that is, chest pain, heart complaints, heart, myocardial infarction, heart attack, heart infarction or common abbreviations of these keywords. Recordings were excluded if (1) they were of poor quality, (2) the conversation was not a triage conversation, (3) patients were <18 years, (4) patients did not live in the vicinity of the OHS-PC, and (4) general practitioners did not want to provide follow-up information including the final diagnosis.Primary and secondary outcome measures The prevalence of dizziness/lightheadedness among patients calling the OHS-PC with acute chest discomfort and the relation between dizziness/lightheadedness and (1) urgency allocation and (2) a final diagnosis of ACS.Results Among 2195 patients who called the OHS-PC with acute chest discomfort, 251 (11.4%) had an ACS (8.3% females, 15.3% males). Females more often reported concurrent dizziness/lightheadedness than males (14.7% vs 10.9%, p=0.008). However, this was not observed in those with confirmed ACS (9.9% of the females vs 9.3% of the males, p=0.881). Reporting of dizziness/lightheadedness was not positively related to an ACS diagnosis in females (OR 0.61 (95% CI 0.31 to 1.21)) or in males (OR 0.82 (95% CI 0.45 to 1.47)). In contrast, both females and males with concurrent dizziness/lightheadedness more often received a high urgency allocation than those without these symptoms.Conclusions Dizziness/lightheadedness are common symptoms but are not positively related to an ACS diagnosis in both females and males with acute chest discomfort. It seems not worthwhile to give females and males with acute chest discomfort and concurrent dizziness/lightheadedness a higher urgency allocation than those without these symptoms.Trial registration number NTR7331.